2008
DOI: 10.1097/ta.0b013e318165c803
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Traumatic Brain Injury in Eastern China, 2004: A Prospective Large Case Study

Abstract: The prospective cohort study shows an alteration of TBI during the past decade in eastern China. It is essential to establish a standardized surveillance system of TBI incidence, risk factors, causes, and outcomes for development of new, more effective, targeted strategies to prevent TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
84
1
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 29 publications
9
84
1
7
Order By: Relevance
“…Traumatic brain injury (TBI) is a leading cause of mortality, morbidity, and in China it is the highest contributor to mortality in adults under 40 years of age (Wu et al., 2008). In addition to primary damages to the brain that occurs immediately following injury, secondary brain injury is highly heterogeneous in presentation and multifactorial in causes (Bramlett & Dietrich, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a leading cause of mortality, morbidity, and in China it is the highest contributor to mortality in adults under 40 years of age (Wu et al., 2008). In addition to primary damages to the brain that occurs immediately following injury, secondary brain injury is highly heterogeneous in presentation and multifactorial in causes (Bramlett & Dietrich, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to the high percentage of traffic accidents, it is expected that more accidents occur outside the home. The results of a study in China showed that almost one-third of traffic accidents were related to motorcycles (15). In this study, motorcycle accident was also the most common cause of road accidents which can be due to increased use of motorcycles in the city as well as very low compliance with traffic rules.…”
Section: Discussionmentioning
confidence: 57%
“…In studies conducted on the entire country, the most common type of accidents was road accidents and then falling (10). In a study conducted in China on brain injuries, 60% of injuries were due to traffic accidents (15). To prevent and reduce accidents, especially traffic accidents, cooperation between various organizations is required and forming committees of safe community, education and awareness, and designing and implementing interventions can be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) remains a leading cause of disability and death in young individuals in China (Wu et al., 2008). Many patients survive; however, they often suffer from poor long‐term outcomes, such as cognitive deficits, because of a lack of effective treatments (Bohnen, Jolles, & Twijnstra, 1992).…”
Section: Introductionmentioning
confidence: 99%